Identification of Safety on Board Purse Seine Vessel (a case study of FV. Mekar baru Putra 3) - Saputra, Rahmad Surya Hadi; Haris, Dendi; Perangin-angin, Robet; Hidayat, Azmi Pebriana (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2024)
The research was conducted in April-May 2023 on the KM. Mekar Baru Putra 3, based at the Pelabuhan Perikanan Nusantara (PPN) Pekalongan. The aim of this study was to identify and evaluate life safety equipment on the purse seine vessel. The research employed a case study approach on the KM. Mekar Baru Putra 3, and data were collected through observations and direct participation in fishing operations on board. Structured interviews were also conducted with fishermen working on the vessel to gather more accurate information regarding life safety equipment. Data analysis was performed using a comparative descriptive approach, comparing the on-board conditions with the minimum requirements for life safety equipment as per applicable regulations. The research findings revealed that the life safety equipment on board included GPS and a fish finder. Based on the evaluation results, a score of 20 was obtained, which is below the minimum threshold specified by the applicable regulations. Therefore, there is a need for awareness and understanding to be conveyed to the owner and captain of the KM. Mekar Baru Putra 3 to ensure compliance with the required life safety equipment